Player-avatar bonds and gaming benefits and risks: Assessing self-discrepancy theory against a broader range of character and play experiences - Jeffrey G. Snodgrass; Seth I. Sagstetter; Julia R. Branstrator; Alessandro Giardina; Michael G. Lacy; Aaunterria Treil Bollinger-Deters; Chaz L. Callendar; Katya Xinyi Zhao; H.J. François Dengah II; Joël Billieux (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2025)
How players relate to their avatars in digital and analog gaming predicts both positive and negative gaming experiences. For example, a perceived discrepancy between one’s actual and avatar self is associated with both gaming benefits and risks. However, such self-discrepancy approaches treat avatars narrowly as self-substitutes that allow players to project idealized identities in a virtual environment. Yet, those approaches have not examined how other kinds of player-avatar bonds—such as avatars experienced as distinct other persons or as impersonal objects used to accomplish gaming goals—might differentially predict gaming benefits and risk of harm. Nor has self-discrepancy research explored how avatar experiences might function in forms of play with positive and negative aspects, e.g., in situations where challenge, suffering, and repeated failure are preconditions for eventual feelings of accomplishment. In the current study, we use ethnographically informed survey responses from North American gamers (N = 149) to examine how a range of player-avatar relationships shape diverse gaming experiences. We find that relating to avatars as self-substitutes, including in situations where players’ experience discrepancies between their actual and avatar selves, does predict gaming benefits and risks, but so do other kinds of player-avatar bonds. Our research thus confirms the importance of self-discrepancy theory in assessments of gaming experience but nonetheless suggests the need for caution if claiming distinctive benefits or risks associated with particular kinds of player-avatar bonds.